Inequality across state lines: how policymakers have failed domestic violence victims in the United States - Sidorsky, Kaitlin N. (Cambridge University Press, 2023)
In the United States, one in four women will be victims of domestic violence each year. Despite the passage of federal legislation on violence against women beginning in 1994, differences persist across states in how domestic violence is addressed. Inequality Across State Lines illuminates the epidemic of domestic violence in the U.S. through the lens of politics, policy adoption, and policy implementation. Combining narrative case studies, surveys, and data analysis, the book discusses the specific factors that explain why U.S. domestic violence politics and policies have failed to keep women safe at all income levels, and across racial and ethnic lines. The book argues that the issue of domestic violence, and how government responds to it, raises fundamental questions of justice; gender and racial equality; and the limited efficacy of a state-by-state and even town-by-town response. This book goes beyond revealing the vast differences in how states respond to domestic violence, by offering pathways to reform.